Pengaruh Personal Branding, Digital Marketing, dan Business Trust terhadap Business Continuity dengan Competitive Advantage sebagai Mediating Variable - Olivia Clarissa; Hani Sirine (INDO PUBLISHING, 2026)
This study aims to analyze the influence of personal branding, digital marketing and business trust on business continuity with competitive advantage as a mediating variable among MSMEs in Central Java. This research is motivated by the importance of marketing strategies and business trust in maintaining business sustainability amid increasing competition and rapid digital transformation. The study employs a quantitative approach using a survey method through questionnaires distributed to MSME actors. Data analysis is conducted using structural Equation Modeling based on Partial Least Squares (SEM – PLS) with SmartPLS software. The result indicate that personal branding, digital marketing, and business trust have a positive and significant effect on competitive advantage. Furthermore, competitive advantage has a positive and significant effect on business continuity. The findings also reveal that competitive advantage significantly mediates the relationship between personal branding, digital marketing, and business trust on business continuity. Therefore, strengthening competitive advantage through effective branding strategies, optimization of digital marketing, and the development of business trust are crucial factors in sustaining MSMEs. This study provides practical implications for MSME actors to optimize digital marketing strategies and build customer trust in order to enhance competitiveness and ensure long-term business sustainability.